Cholesterol and Blood Profile of Bali Cattle Fed Chromolaena odorata Weed with Rice Straw as Basal Feed - Gustaf Oematan; Marthen Luther Mullik; Imanuel Benu; I Gusti Ngurah Jelantik; Twenfosel Dami Dato; Gusti Ayu Yudit Lestari; Gemini Ermiani Malelak; Erna Hartati; Edwin Lazarus; Marten Yunus (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to determine the effect of the level of C. odorata (CO) silage-based concentrate on the blood profiles of Bali cattle. Three male Bali cattle (initial 2 years old with CV = 19,28%) were randomly assigned to one of three meals: rice straw and concentrates containing C.odorata silage 30% (RCO30) or  C.odorata silage 40% (RCO40) or C.odorata silage 50% (RCO50), respectively, using a 3 x 3 Latin Square Design. The was no significant effect between treatments (P> 0.05) on blood cholesterol (195.74-220.49 mg/dL), blood urea (48.41-49.44 mg/dL), total blood plasma (6.08-6.93 g/dL), blood haemoglobin (Hb; 18.18-18.92 g/dL), hematocrit levels (45.56-53.03%), erythrocytes (7.06-8.24 106/l), and leucocytes (8.56-8.84/l). Blood glucose levels, however, differed significantly (P<0.05) between treatment. Feeding Bali cattle with different levels of C.odorata-based concentrate resulted in the same effect on all blood parameters except blood glucose. Therefore, it is recommended that the use of C.odorata in a ration of Bali cattle can be up to 50%.